2009
DOI: 10.1002/lary.20171
|View full text |Cite
|
Sign up to set email alerts
|

Arytenoid adduction with medialization laryngoplasty versus injection or medialization laryngoplasty: The role of the arytenoidopexy

Abstract: AA-ML and IL/ML improve phonatory function, but not to normal. We were unable to demonstrate a statistical difference between groups using a single measure, but using mutlivariate analysis, there is a statistical significance between the groups. AA-ML patients had worse preoperative function and had better postoperative function. When clinically indicated, AA-ML procedure does appear to correct the physiology of the incompetent larynx better than ML alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 15 publications
1
57
1
1
Order By: Relevance
“…216 These are focused around improving VF approximation by improving efficiency of the weakened system with behavioral management. 225,230,245 The goal of voice therapy is to improve glottal closure without supraglottic hyperfunction by development of abdominal support for breathing and intrinsic muscle strengthening exercises. These may be effective interventions as a temporary improvement until normal voice recovers, may aid in selection of patients for surgical intervention, or may provide the essentials for long-term rehabilitation.…”
Section: Action Statement Profilementioning
confidence: 99%
“…216 These are focused around improving VF approximation by improving efficiency of the weakened system with behavioral management. 225,230,245 The goal of voice therapy is to improve glottal closure without supraglottic hyperfunction by development of abdominal support for breathing and intrinsic muscle strengthening exercises. These may be effective interventions as a temporary improvement until normal voice recovers, may aid in selection of patients for surgical intervention, or may provide the essentials for long-term rehabilitation.…”
Section: Action Statement Profilementioning
confidence: 99%
“…Mortensen et al also looked at AA with Th versus Th alone but looked at objective outcome measures only. 4 In comparing the two groups, they found that the combined-procedure group had worse preoperative average phonatory function and that there were no significant differences in outcome postoperatively. When comparing the improvement in outcome, they did find significantly greater improvement in the combined-procedure group.…”
Section: Discussionmentioning
confidence: 96%
“…AA requires extra surgical time, and increased complication rates have been reported. 3,4 Although studies have shown that AA provides good posterior glottic closure, no study has demonstrated that it creates better closure than Th alone. 5 Studies measuring patient's perception of vocal function along with objective acoustic measures comparing Th alone with Th plus AA have not reached any definitive concensus.…”
Section: Introductionmentioning
confidence: 99%
“…The most common phonosurgical procedures used today are: injection augmentation, medialization thyroplasty, and arytenoid adduction (AA). 2,3 When using an external approach through the thyroid cartilage as in medialization thyroplasty, only the anterior membranous part of the vocal fold can be medialized. 4,5 To close the posterior glottis and/or correct level differences of the vocal folds, an AA can be performed together with medialization thyroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…The major drawback is the difficult accessibility of the muscular process deserving a demanding surgical procedure with significant increased morbidity including hypopharyngeal perforation, postoperative respiratory distress, and tracheotomy. 3,5 To overcome these difficulties, several modifications of the AA procedure have been proposed, for example, the resection of the posterior rim of the thyroid plate or pulling on the LCA muscle through a thyroid window. 6,7 Based on our former anatomical studies it should be possible to get access to the muscular process of the arytenoid cartilage through a standard medialization thyroplasty window.…”
Section: Introductionmentioning
confidence: 99%